A study of the experiences of vocational students learning functional mathematics in further education colleges - Dalby, D.M. (2015)
The education system in England has long been characterised by a distinct separation between academic or vocational pathways in the post-16 phase. Until recent policy changes this division coincided with the point at which compulsory education ended and mathematics became an optional subject for many students. Those who failed to attain the widely accepted minimum standard of a grade C in GCSE mathematics, however, were often strongly encouraged to undertake a course to improve their mathematical knowledge and skills. This study focusses aged 16-19 and examines the learning experience of those who take a functional mathematics course alongside their vocational programme, as either a recommended option or a requirement of internal college policy.